Neurofilament light chain level in traumatic brain injury: A system review and meta-analysis. Issue 38 (18th September 2020) - Gao, Wenyan; Zhang, Zhongshan; Lv, Xiaoling; Wu, Qing; Yan, Jing; Mao, Genxiang; Xing, Wenmin
Abstract: Background: Neurofilament light (NfL) level was obviously increased in traumatic brain injury (TBI) individuals. But, no comprehensive meta-analysis has ever been conducted to assess the diagnostic performance of NfL. This study aims to evaluate the relationship between NfL level and TBI through a meta-analysis. Methods: Studies were selected from Pubmed, Web of science, Embase, Google Scholar, PMC and Chinese National Knowledge Infrastructure (CNKI), and the Chinese Biomedical Literature Database (CBM) through inclusion and exclusion criteria. The standard mean difference (SMD) and 95% confidence interval (CI) were calculated using the random-effect model or fixed-effect model to assess the association between NfL level and TBI. Subgroup analysis according to sample collection time, sample type and detection method was performed. The influence analysis and publication bias was also conducted. All analyses were performed using the RevMan 5.3 and Stata 12 software. Results: A total of 9 studies were included. Results indicated that TBI individuals had a higher NfL expression level compared with the non-TBI individuals (SMD = 2.48, 95% CI = 1.52–3.43, I 2 = 96%, P < .01). Similar NfL increasing was also observed in Caucasian population, 0–48 hour and 6–10 days sample collection time, as well as cerebrospinal fluid (CSF), serum, plasma sample subgroup analysis. Moreover, the NfL increasing still existed no matter the NfL expression level was detected by ELISA or Simoa assay. Conclusion: NfL expression level was increased in TBI individuals, which indicated that NfL could be a potential biomarker in the diagnosis of TBI and other neurodegenerative diseases.